Subcutaneous Rituximab-MiniCHOP Compared With Subcutaneous Rituximab-MiniCHOP Plus Lenalidomide in Diffuse Large B-Cell Lymphoma for Patients Age 80 Years or Older. Issue 11 (10th April 2021) - Oberic, Lucie; Peyrade, Frederic; Puyade, Mathieu; Bonnet, Christophe; Dartigues-Cuillères, Peggy; Fabiani, Bettina; Ruminy, Philippe; Maisonneuve, Hervé; Abraham, Julie; Thieblemont, Catherine; Feugier, Pierre; Salles, Gilles; et al.
Abstract : PURPOSE: The prognosis of elderly patients with diffuse large B-cell lymphoma (DLBCL) is worse than that of young patients. An attenuated dose of chemotherapy—cyclophosphamide, doxorubicin, vincristine, and prednisone plus rituximab (R-miniCHOP)—is a good compromise between efficacy and safety in very elderly patients. In combination with R-CHOP (R2-CHOP), lenalidomide has an acceptable level of toxicity and may mitigate the negative prognosis of the non–germinal center B-cell–like phenotype. The Lymphoma Study association conducted a multicentric, phase III, open-label, randomized trial to compare R-miniCHOP and R2-miniCHOP. PATIENTS AND METHODS: Patients of age 80 years or older with untreated DLBCL were randomly assigned into the R-miniCHOP21 group or the R2-miniCHOP21 group for six cycles and stratified according to CD10 expression and age. The first cycle of rituximab was delivered by IV on D1 after a prephase and then delivered subcutaneously on D1 of cycles 2-6. Lenalidomide was delivered at a dose of 10 mg once daily on D1-D14 of each cycle. The primary end point was overall survival (OS). RESULTS: A total of 249 patients with new DLBCL were randomly assigned (127 R-miniCHOP and 122 R2-miniCHOP). The median age was 83 years (range, 80-96), and 55% of the patients were classified as non-GCB. The delivered dose for each R-miniCHOP compound was similar in both arms. Over a median follow-up of 25.1 months, the intention-to-treat analysis revealed that R2-miniCHOP did not improve OS (2-year OS 66% in R-miniCHOP and 65.7% in R2-miniCHOP arm, P = .98) in the overall population or in the non-GCB population. Grade 3-4 adverse events occurred in 53% of patients with R-miniCHOP and in 81% of patients with R2-miniCHOP. CONCLUSION: The addition of lenalidomide to R-miniCHOP does not improve OS. Rituximab delivered subcutaneously was safe in this population.